2021
DOI: 10.33448/rsd-v10i10.18427
|View full text |Cite
|
Sign up to set email alerts
|

Relação do ácido linoleico e alfa linolênico na alimentação de aves de postura: Uma revisão

Abstract: O uso de lipídios na alimentação das aves é uma estratégia nutricional muito utilizada, pois contribui com o incremento energético, fornece importantes nutrientes para um equilíbrio nutricional e é a principal fonte de ácidos graxos poliinsaturados. Os poliinsaturados compreende as famílias de ácidos graxos ômega-3 e ômega-6. Onde seus principais representantes são os ácidos linoléico, alfa-linolênico, ácidos araquidônico e docosaexaenoico.  Esses ácidos vêm sendo bastante estudados devido a suas diversas funç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The experimental diets were formulated to contain the same metabolizable energy, so as the level of cactus pear increased, it was necessary to increase the amount of soybean oil in the feed to standardize the metabolizable energy. Soybean oil has a reasonable amount of linolenic acid [56], and this acid promotes increased concentrations of estrogen, which is important in controlling egg weight since dietary fats influence egg weight [57,58]. The authors [57] found that diets with supplemental fat and linoleic acid increased the albumen weight of eggs of Isa Brown hens from the 22nd to 65th week of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental diets were formulated to contain the same metabolizable energy, so as the level of cactus pear increased, it was necessary to increase the amount of soybean oil in the feed to standardize the metabolizable energy. Soybean oil has a reasonable amount of linolenic acid [56], and this acid promotes increased concentrations of estrogen, which is important in controlling egg weight since dietary fats influence egg weight [57,58]. The authors [57] found that diets with supplemental fat and linoleic acid increased the albumen weight of eggs of Isa Brown hens from the 22nd to 65th week of age.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of soybean oil in the diet increased the linoleic and linolenic acid contents and, consequently, increased the linoleic and α-linolenic fatty acids in the yolk [56]. Linoleic acid promotes increased estrogen concentrations and, thus, stimulates protein synthesis in the oviduct, causing greater protein deposition in the albumen, resulting in a heavier egg [58]. In addition, linoleic acid has long been accepted as having a hypocholesterolemia effect and inhibitory properties against metastatic colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%